MUTATION ANALYSIS FOR NUCLEOPHOSMIN-1 (NPM1) GENE VARIANT OF CHRONIC MYELOID LEUKEMIA PATIENTS FROM LAHORE-PAKISTAN - Sumaira Mehboob; Kokab Durri; Muhammad Farooq Sabar; Hira Muzzamal; Farkhanda Manzoor (International Journal of Pharmacy & Integrated Health Sciences)
Background: Chronic Myeloid Leukemia (CML) is a malignant genetic disorder commonly caused by the translocation of two genes among chromosomes 9 and 22. Nucleophosmin1 (NPM1) is a nuclear protein-coded gene located on chromosome 5q35. NPM1 protein, in association with other tumor suppressor proteins, prevents cell proliferation in an uncontrolled way. Several mutations are located within exon 12 of the NPM1 gene. More than 95% of these mutations are frameshift due to the insertion of tetra‐nucleotides at positions 863 and 864 of exon 12. Three common mutation types (A, B, and D) represent about 90% of NPM1 mutations. Objectives: To analyze the NPM1 gene variants and their association with CML. Methodology: Genomic DNA was extracted from the whole blood of 50 cases and health control subjects. NPM1 (563 bp) was amplified using gene-specific primers by PCR and sequenced using BigDye® Terminator. The mutation was analyzed using Sanger sequencing in an ABI Gene Analyzer (3130XL). The results were analyzed and compared with the reference human NPM1 gene (accession # NG_016018.1). Results: The gene sequencing analysis revealed that NPM1 mutation (type A: Dup TCTG) was not present in DNA-sequenced samples of CML patients. Conclusion: It may be concluded that NPM1 mutations are unlikely to be linked to CML illness in a Pakistani community. Further research with a larger sample size may aid in determining the role of other gene mutations with CML for the effective treatment of this cancer.